Strategi Komunikasi Pemerintah Dalam Upaya Penanganan Sampah Rumah Tangga Di Kawasan Penfui Timur, Kupang - Donna Isra Silaban; Yohannes Viser (Universitas Informatika dan Bisnis Indonesia, 2020)
This study aims to examine communication strategies in the government's efforts to deal with waste problems. This study aims to: (1) Determine the volume of household waste in the East Penfui area, Kupang, (2) Evaluate ways of handling household waste problems in the East Penfui area so that it can overcome garbage problem that occurs. This type of research is qualitative research. The objects studied were 4 points of garbage accumulation on Jalan Herman Johanes, Prof. Dr. and the sample used is the number of households in the village of East Penfui. The data in this study were obtained by conducting surveys, documenting and interviewing people who live in the village of East Penfui. Data analysis techniques using case study analysis techniques. The results obtained from this study are: (1) the average waste generation is 6.2 liters / person / day, the volume of community waste generation is 24.81 liters / family / day; (2) The methods for handling waste problems that have been carried out by the people of East Penfui Village are not yet appropriate and correct, so it is necessary to provide counseling or socialization on how to handle waste problems properly and correctly. The way to minimize the volume of waste generated by the community is by providing 186 units of trash cans with a capacity of 140 L which can accommodate 6 households of garbage per unit. The frequency of garbage collection that must be done is every 3 days.